Factors and Effect of Social Assistance Information to Donor Decision for NGO Crowdfunding in Indonesia - Husin Ali; Roy Valiant Salomo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to find out the effect of social assistance information given by Non-Governmental Organizations (NGO) for donor decision to crowdfunding in Indonesia. Also find a relationship between the predicted factors (public trust, donor altruism, government participation) that related to the effectiveness of information that comes from the government and donor decision after social assistance information by Non-Governmental Organizations (NGO). The approach used in this research is a quantitative approach. The data used in this study are primary data, collected by using the interview method with a questionnaire. The sampling technique used is non-probability sampling with purposive sampling technique. The sample taken 200 respondents in various place in Indonesia.  Data analysis techniques of this study are descriptive analysis techniques and Structural Equation Modeling (SEM) analysis techniques. The scale used in this study is a Likert scale. The results showed that social assistance information given by Non-Governmental Organizations (NGOs) has a positive effect on donor decision for crowdfunding in Indonesia.